Estilos de aprendizaje y la lecto escritura en estudiantes de la Escuela de Educación General Básica “San Felipe Neri” - Jácome Jaña, Lizbeth Estefanía (2023)
The objective of this research work is to demonstrate the influence of learning styles on the literacy of second-year students of primary education at the "San Felipe Neri" General Basic Education School in the city of Riobamba; the learning styles today have served to make significant changes in the teaching-learning process. In addition, it allows us to understand the diversity of the human being, where each person is a different world, and therefore, the learning process is carried out differently. The ways of teaching-learning cannot be defined as correct or incorrect; however, when difficulties are evident in the literacy process in children and not attended to, the problems persist or increase in subsequent school years. The research methodology presents a quantitative approach since the process complied with a sequence of systematic steps from identifying the problem to information collected through the psychometric technique with the data collection instruments, the "VAK" test for analysis. The "TALE" test was applied to analyze literacy, using tools that have proven valid and reliable in previous studies. The results obtained in the VAK test on learning styles reveal that most students present a kinesthetic learning style, and a minority percentage learn visually and auditorily. In the TALE test on the acquisition of literacy, there needs to be an adequate level in most students, both in reading and writing, corresponding to the first level or first year of primary education. During the processing of the information, the statistical program SPSS and Excel were used, which helped to obtain the following results: a Pearson correlation of .405*and a bilateral significance of .040 could be evidenced. Learning styles have a positive impact on the development of students' literacy. Concluding that the more learning styles the students strengthen, they develop more skills for the acquisition and strengthening of literacy.